Phytochemical analysis and in vitro anthelmintic activity of Imperata cylindrica underground parts - Pawi Bawitlung Lalthanpuii; Kholhring Lalchhandama (BMC, 2020)
Abstract Background Imperata cylindrica is considered as an agricultural weed, but it is a valuable plant in the traditional medicines of Southeast Asia. In the Mizo traditional medicine of India and Myanmar, the rhizomes and roots are used as a remedy for bacterial, fungal and intestinal helminth infections. Methods An extract of the whole underground parts was prepared in Soxhlet apparatus using chloroform as a solvent. After concentrating in a vacuum rotary evaporator, the extract was analysed using gas chromatography-mass spectrometry. Anthelmintic activity was tested in vitro against the tapeworm Raillietina tetragona and the roundworm Ascaridia galli. Scanning electron microscopy was used to examine the structural changes on the helminths after treatment with the plant extract. Results Twenty-two compounds were identified from the plant extract out of which fatty acids were the predominant compounds. Palmitic acid was the most abundant. Bioactive phytosterols such as campesterol and stigmasterol were also detected. The plant extract was significantly effective on both the helminths and showed dose-dependent anthelmintic activity as that of albendazole. The tapeworm treated with the plant extract showed deformities on the suckers, clumping of the spines, tegumental folds and erosion of microtriches. Extensive damage was also seen on the roundworm including cuticular shrinkage, collapse of the lips, and formation of warty surface throughout the body. Conclusion I. cylindrica extract effectively killed and caused detrimental effects on parasitic tapeworm and roundworm. The study therefore validates the traditional usage among the Mizo people, and guarantees further investigation on the exact compound(s) and mechanism of action.